(untitled) (Journal of the College of Basic Education, 2022)
Peroxidase was extracted from Prickly lettuce (Lactuca serriola L.) by used sodium phosphate buffer 0.1 M which content 1 mM L-cysteine and 0.1 gm Polyclar AT. crude enzyme was concentrated by gradual addition of ammonium sulfate at 40-80% saturation, the specific activity, fold of purification and yield were 6673 unit/mg, 2.5 and 74.37% respectively. Then purified throw ion exchange chromatography by DEAE-cellulose, the specific activity, fold of purification and yield were 11961 unit/mg, 4.5 and 27.46% respectively, and gel filtration through Sephacryl S-200, the specific activity, fold of purification and yield were 15496 unit/mg, 5.8 and 23.24% respectively.